2013
DOI: 10.1186/1742-4933-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Slower immune system aging in women versus men in the Japanese population

Abstract: BackgroundGender-related differences in humans are commonly observed in behaviour, physical activity, disease, and lifespan. However, the notion that age-related changes in the immune system differ between men and women remains controversial. To elucidate the relationship between immunological changes and lifespan, peripheral blood mononuclear cells from healthy Japanese subjects (age range: 20–90 years; N = 356) were analysed by using three-colour flow cytometry. The proliferative activities and cytokine-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
117
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 24 publications
16
117
2
3
Order By: Relevance
“…The authors reported age-related declines in T and B cell numbers as well as changes in CD4 + /CD8 + T cell ratios. The rate of decline in B and T cell numbers, increases in the CD4 + / CD8 + T cell ratio, and increases in NK numbers were significantly greater in males versus females (120).…”
Section: Sex-dependent Changes In the Aging Immune Systemmentioning
confidence: 92%
“…The authors reported age-related declines in T and B cell numbers as well as changes in CD4 + /CD8 + T cell ratios. The rate of decline in B and T cell numbers, increases in the CD4 + / CD8 + T cell ratio, and increases in NK numbers were significantly greater in males versus females (120).…”
Section: Sex-dependent Changes In the Aging Immune Systemmentioning
confidence: 92%
“…T EMRA s [8,[105][106][107]. At the same time, a larger proportion of older men experience an inverted CD4/CD8 T cell ratio as compared to women of the same age [107].…”
Section: Cells and T Cells (Particularly Cd4+ T Cells And Mucosal Assmentioning
confidence: 94%
“…At the same time, a larger proportion of older men experience an inverted CD4/CD8 T cell ratio as compared to women of the same age [107]. The proliferative and cytokinesecretion capacity of T cells isolated from older men is diminished more so than in cells isolated from older women, as is the ability of monocytes to secrete IFN-c-inducible protein 10 (IP-10), a chemoattractant for activated T cells [13,105,107,108]. The increased accumulation of NK cells in older women is an exception to this general pattern [105].…”
Section: Cells and T Cells (Particularly Cd4+ T Cells And Mucosal Assmentioning
confidence: 99%
“…in Japan 85.5 years in women and 79.0 in men [10]. A sexual dimorphism in the immune response means that females are more resistant to infections but they have higher incidence of autoimmune diseases compared to male [12]. This aged woman revealed poor prognosis from IP with MPO-ANCA associated vasculitis, probably due to immunological impairments.…”
Section: Discussionmentioning
confidence: 99%